Wellens syndrome: from involvement of the anterior descending artery to percutaneous coronary revascularization. - Montiel Alfonso, Miguel Angel; Ávalos Larroza, Jorge; García Morínigo, Elder; Duarte Samudio, Nancy (Medicina Clínica y Social, 2025)
Wellens syndrome is an entity characterized electrocardiographically by the presence of inverted or biphasic T waves in right precordials. It is an unstable angina subtype with a high risk of progressing to acute myocardial infarction on the anterior face. Its finding predicts with high sensitivity and specificity the involvement of the proximal portion of the anterior descending artery, requiring an early invasive strategy to avoid complications. The following is a case of a patient with different electrocardiographic manifestations who was taken to the hemodynamic laboratory for percutaneous coronary artery revascularization by involvement of the anterior descending artery.